2021
DOI: 10.1111/1365-2745.13796
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐year drought alters plant species composition more than productivity across northern temperate grasslands

Abstract: 1. The occurrence of multi-year drought is predicted to increase globally with climate change. However, it is unclear whether drought effects on ecosystems are progressive through time.2. Here, we experimentally reduced growing season precipitation (GSP) by 45% at seven North American temperate grasslands for four consecutive years to determine the following: (a) whether the effects of reduced precipitation on plant community structure and biomass components (shoot, root, litter) are compounding over time; (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…Plant productivity at the field experiment sites ranged from 33.6 to 492.3 g/m 2 and species richness from 4.0 to 18.0 species/ m 2 , with no relationship between the two community characteristics among sites (see Appendix S1: Figure S2). Previous research using a subset of these sites also found no effect of drought on plant diversity and inconsistent effects on productivity (Batbaatar et al, 2021), suggesting that precipitation history, diversity, and productivity effects on SBRs may be evaluated independently. We calculated the treatment averages of total biomass, the root mass fraction, as well as Pascopyrum and Vicia biomass by field site.…”
Section: Sitementioning
confidence: 85%
See 2 more Smart Citations
“…Plant productivity at the field experiment sites ranged from 33.6 to 492.3 g/m 2 and species richness from 4.0 to 18.0 species/ m 2 , with no relationship between the two community characteristics among sites (see Appendix S1: Figure S2). Previous research using a subset of these sites also found no effect of drought on plant diversity and inconsistent effects on productivity (Batbaatar et al, 2021), suggesting that precipitation history, diversity, and productivity effects on SBRs may be evaluated independently. We calculated the treatment averages of total biomass, the root mass fraction, as well as Pascopyrum and Vicia biomass by field site.…”
Section: Sitementioning
confidence: 85%
“…That SBRs were typically positive but independent of soil origin suggests that Vicia may not be specific in its association with beneficial soil microbes. This suggests that subordinate species may be able to compensate for drought legacy effects if the dominant species relies on drought sensitive soil biota (Mariotte et al, 2015), which can result in altered plant composition as seen in the field for a subset of our sites (Batbaatar et al, 2021). That Vicia was strongly affected by drought in both live and sterile soils, however, suggests soil biota benefits are insufficient to allow persistence through drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, numerous studies show that drought alters plant community diversity in many ways (genetic, species, functional and growth form). These studies often infer that plant community attributes, before and after drought, mediate drought sensitivity (Batbaatar et al., 2022; Gottschall et al., 2023; Griffin‐Nolan, Blumenthal, et al., 2019; Harrison et al., 2018; Korell et al., 2021; Liu, Wang, et al., 2022; Mackie et al., 2019; Peñuelas et al., 2007; Shaw et al., 2022; Tilman & El Haddi, 1992; Van Ruijven & Berendse, 2010). Some experiments have explicitly tested for interactions between various components of biodiversity and drought via the independent manipulation of both (e.g.…”
Section: How Can Drought Experiments Be Improved?mentioning
confidence: 99%
“…The ecological impacts of drought are most often assessed from single site‐level studies of natural drought (Ignacio et al, 2022) or, less often, across multiple sites spanning a regional precipitation gradient (Batbaatar et al, 2021; Cherwin & Knapp, 2012; Knapp et al, 2015). However, the sensitivity of grasslands to extreme drought is expected to differ between sites, regions, and continents, given their differences in evolutionary history, community structure, precipitation regimes, temperature variability, and soil properties (Smith et al, 2022).…”
Section: Introductionmentioning
confidence: 99%